Influence of low-symmetry distortions on electron transport through metal atom chains: when is a molecular wire really "broken"? - Georgiev, V; McGrady, J (2011)
In the field of molecular electronics, an intimate link between the delocalization of molecular orbitals and their ability to support current flow is often assumed. Delocalization, in turn, is generally regarded as being synonymous with structural symmetry, for example, in the lengths of the bonds along a molecular wire. In this work, we use density functional theory in combination with nonequilibrium Green's functions to show that precisely the opposite is true in the extended metal atom chain Cr(3)(dpa)(4)(NCS)(2) where the delocalized π framework has previously been proposed to be the dominant conduction pathway. Low-symmetry distortions of the Cr(3) core do indeed reduce the effectiveness of these π channels, but this is largely irrelevant to electron transport at low bias simply because they lie far below the Fermi level. Instead, the dominant pathway is through higher-lying orbitals of σ symmetry, which remain essentially unperturbed by even quite substantial distortions. In fact, the conductance is actually increased marginally because the σ(nb) channel is displaced upward toward the Fermi level. These calculations indicate a subtle and counterintuitive relationship between structure and function in these metal chains that has important implications for the interpretation of data emerging from scanning tunnelling and atomic force microscopy experiments.